Neonatal small left colon syndrome: a case report - Gündoğdu, Hülya; Tanyel, F. Cahit; Besim, Aytekin; Büyükpamukçu, Nebil (The Turkish Journal of Pediatrics, 1990)
A newborn infant with neonatal small left colon syndrome is presented, and the relevant literature regarding the etiology of the disorder, its diagnosis and follow-up treatment is reviewed.